PERAN PEREMPUAN DAN STRATEGI KEBERLANJUTAN NAFKAH RUMAHTANGGA PETANI HORTIKULTURA KABUPATEN KONAWE - Israwati Israwati; Saediman Saediman; Nur Rahmah (Universitas Halu Oleo, 2018)
This study was done in Lalonggotomi and Ahuawatu village, Pondidaha subdistrict of Konawe Regency with purposes: described the role of woman in horticultural farmer’s household in Konawe Regency; described the strategy used for the household expenses continuity of horticultural farmer in Konawe regency. The results of the research were: the woman role in Lalonggotomi and Ahuawatu was fairly high with 84%, this showed that woman who do an activity such as reproductive, productive and social reached 84% from total number of informant; strategy done for the continuity of household expenses were: Creation of farming expenses source with the utilization of farming sector effectively and efficiently, increasing number of employee, the us of recent technology innovation and land expension; double expenses pattern, beside helping the husband to work in the farm. there were also daily necessity’s shop, catering, and vegetable distributor, sewing and rise selling; the utilization of loan; and asset utilization.Keywords: woman’s role; household expenses; continuity strategy